ANALISIS DINAMIK PENYEBARAN HUMAN PAPILLOMAVIRUS DENGAN PENGARUH VAKSINASI DAN SKRINING - Miftakhul Rosidah; Heni Widayani; Usman Pagalay (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Cervical cancer caused by Human Papillomavirus (HPV) is a serious health problem in Indonesia. The spread of HPV is still an unresolved problem even though a vaccine has been found and screening has been carried out in health facilities in Indonesia. In this study, the dynamic analysis of the HPV spread model was studied by categorizing the population into 6 sub-populations, namely the susceptible individual population (S(t)), the vaccinated individual population (V(t)), the infected individual population who were not aware 〖(I〗_u (t)), population of infected and screened individuals 〖(I〗_s (t)), population of individuals exposed to cervical cancer (C(t)), and population of cured individuals (R(t)). The model describes the dynamic rate of HPV spread which has two equilibrium points, namely the disease-free equilibrium point and the endemic equilibrium point. The results of this study indicate that the disease-free equilibrium point is unstable, meaning that there is still a possibility that infection will occur in the population. The numerical simulation illustrates that the percentage of individuals who are vaccinated will reduce the increase in the number of unconscious infected individuals and individuals with cervical cancer. Increasing the screening rate in the population will also reduce the number of unconsciously infected individuals and individuals with cervical cancer.